Future Changes in Simulated Streamflow in Costa Rica from CMIP6 climate models - Hidalgo León, Hugo G. (2022)
Statistically downscaled daily data from an ensemble of five General Circulation Models (GCMs) from the Climate Model Intercomparison Program 6 (CMIP6) will be used to determine changes (with respect to a baseline historical scenario) in the magnitude of the 20-year return period streamflow for 34 basins covering Costa Rica at horizons corresponding to mid-century and end-of-century. The climate models used were selected according to Almazroui et al. (2021), which proved to have the lower biases in reproducing the region’s climate. The chosen downscaling method corresponds to a delta approach described in Navarro-Racines et al. (2020). The hydrological simulations were computed using the HBV model. The concentration scenario selected for this study is SSP5-8.5, considered a pessimistic scenario. Preliminary results show precipitation increases in the Pacific Slope, however, the increases in actual evapotranspiration due to warming over exceeds the precipitation effects, causing a future reduction in streamflow in basins in the Pacific Slope and reductions in the Northern Caribbean region of Costa Rica. This is important as it suggests that the North Pacific, a climatologically drier region, will experience significant increases in aridity. This region is known to present social and economic vulnerabilities, as it is part of the Central American Dry Corridor.